Imaging liver lesions using grating-based phase-contrast computed tomography with bi-lateral filter post-processing - Herzen, Julia; Willner, Marian S.; Fingerle, Alexander A.; Noel, Peter B.; Koehler, Thomas; Drecoll, Enken; Rummeny, Ernst J.; Pfeiffer, Franz (PLoS ONE, 2014)
X-ray phase-contrast imaging shows improved soft-tissue contrast compared to standard absorption-based X-ray imaging. Especially the grating-based method seems to be one promising candidate for clinical implementation due to its extendibility to standard laboratory X-ray sources. Therefore the purpose of our study was to evaluate the potential of grating-based phase-contrast computed tomography in combination with a novel bi-lateral denoising method for imaging of focal liver lesions in an ex vivo feasibility study. Our study shows that grating-based phase-contrast CT (PCCT) significantly increases the soft-tissue contrast in the ex vivo liver specimens. Combining the information of both signals - absorption and phase-contrast - the bi-lateral filtering leads to an improvement of lesion detectability and higher contrast-to-noise ratios. The normal and the pathological tissue can be clearly delineated and even internal structures of the pathological tissue can be visualized, being invisible in the absorption-based CT alone. Histopathology confirmed the presence of the corresponding findings in the analyzed tissue. The results give strong evidence for a sufficiently high contrast for different liver lesions using non-contrast-enhanced PCCT. Thus, ex vivo imaging of liver lesions is possible with a polychromatic X-ray source and at a spatial resolution of ∼100 μm. The post-processing with the novel bi-lateral denoising method improves the image quality by combining the information from the absorption and the phase-contrast images. © 2014 Herzen et al.
CRIS-Team Scopus Importer:2023-03-08